Pengembangan Media Pop-Up Book IPAS Berbasis Living Values Education Program untuk Peserta Didik SD - Harwati, Tantri; Apriani, An-Nisa; Sari, Indah Perdana; Shidiq, Galih Albarra (Indonesian Journal of Elementary Education and Teaching Innovation, 2024)
Religious character is important to be applied from an early age to prevent moral decadence. Inserting or incorporating religious characters can be done in learning activities by using learning media. Pop-up book media is a book-shaped media with a real-like image display and can move. Meanwhile, LVEP is a value education that offers value activities so that students are able to explore and develop life values. The purpose of this research is to produce LVEP-based IPAS pop-up book media to improve religious character, teacher and student responses to the media. LVEP-based IPAS pop-up book media uses the 4D model which goes through 4 stages, namely the defining stage (define), the planning stage (design), the development stage (development), and the dissemination stage (disseminate). The data collection technique is qualitative from the results of interviews and quantitative data from the validation of material experts, media experts and teacher and student responses. Interviews were conducted with one class teacher, validation by one material expert, one media expert and 9 students. On the validation of the material that gets an average score of 4.6 with the category "Very Good" comes from the feasibility of presentation 3.9 and the feasibility of language 4. While the media validation obtained an average score of 3.95 with the category "Good" which comes from the feasibility of language of 4.5 plus the feasibility of language 4.8 and the feasibility of language 4.8. and feasibility of supporting learning 4.7. After that, an assessment was carried out to find out the responses of teachers and students to the LVEP-based IPAS pop-up book. The results of the teacher's assessment received a response with an average score of 4 with the category "Good" and the response given by students was 87% with the criteria "Very Good". Based on the results of the validation recapitulation, the LVEP-based IPAS pop-up book is suitable for use to improve the religious character of elementary school students. This research can be developed again or as reference material for further researchers in similar studies.